WORKSHOP PENULISAN ARTIKEL ILMIAH BAGI GURU MIPA - Baiq Rika Ayu Febrilia; Eliska Juliangkary; Sri Yuliyanti; Dwi Sabda Budi Prasetya; Pujilestari Pujilestari; Dwi Utami Setyawati (LP2M Universitas Hasanuddin, 2020)
Scientific Article Writing Workshop for MIPA Teachers at Al-Abhariyah Islamic Vocational SchoolAbstract. This community service aims to help teachers better understand writing techniques, increase understanding of scientific articles and develop professionalism as instructors through scientific article writing activities. The method in community service activities is to provide workshops to Islamic Mathematics and Natural Sciences Al-Abhariyah Vocational School teachers on writing scientific articles. The results of community service show that participants have the ability to understand the techniques of writing scientific articles, distinguish scientific articles from scientific works and have the desire to conduct research even though it has not been realizedKeywords: Workshop, scientific articles, mathematics and natural sciences teachersAbstrak. Pengabdian masyarakat ini bertujuan untuk membantu guru agar lebih memahami artikel ilmiah secara teoritis baik dari segi karakteristiknya maupun teknik penulisannya, serta mampu membedakan artikel ilmiah, skripsi dan tesis. Metode dalam kegiatan pengabdian kepada masyarakat adalah dengan memberikan workshop kepada guru MIPA SMK Islam Al-Abhariyah tentang penulisan artikel ilmiah. Hasil pengabdian kepada masyarakat menunjukkan peserta telah memiliki kemampuan untuk memahami teknik penulisan artikel ilmiah, membedakan artikel ilmiah dengan karya ilmiah serta telah memiliki keinginan melakukan penelitian walaupun belum terealisasikan.Kata Kunci: Workshop, artikel ilmiah, guru MIPA